The Descent of Some Chester Libraries. (15th March 2021) - Hanna, Ralph
Abstract: In his grand Medieval Manuscripts in British Libraries, Neil Ker identified, in two different repositories, the extensive remains of a single sixteenth-century library. This had clearly been gathered together before the Dissolution from the book collections of a variety of religious houses, all of those identifiable in the city of Chester. The essay traces the probable passage of these volumes from their initial collection to their present repositories, Gray's Inn and Shrewsbury School. In this account, the initial collector, William Wall, eventually prebendary of Chester Cathedral, had passed these on to a recusant family, the Egertons, and they, in turn, descended through an illegitimate daughter to the Bostocks, who donated them to their present institutions.